A influência do maoísmo na redefinição da Linha Geral da Ação Popular (AP) para a revolução brasileira - Reginaldo Benedito Dias (Nuevo mundo - Mundos Nuevos, 2024)
In 1968, Ação Popular (AP), a Brazilian revolutionary organization, embraced Maoism, though the implications of this affiliation were not uniform. Intense controversies emerged regarding its significance, leading to conflicting theses, disputes, and organizational splits. Through bibliographic and documentary analysis, this study examines how Maoism influenced the formulation of AP's General Line for the Brazilian revolution, highlighting the variations present in internal debates and the struggles between its factions